A new approach to compare the predictive power of metabolic syndrome defined by a joint interim statement versus its components for incident cardiovascular disease in Middle East Caucasian residents in Tehran. Issue 5 (4th November 2010) - Hadaegh, F; Zabetian, A; Khalili, D; Safarkhani, M; Philip T James, W; Azizi, F
Abstract : Background: Metabolic syndrome (MS) has an increased risk for developing cardiovascular disease (CVD); however, whether the concept of MS, applying the new joint interim statement definition, has a greater impact on incident CVD than its individual components is debated. Methods: The authors related MS and its components to CVD incidence in 1856 men and 2392 women, Iranian adults aged ≥40 years, free of CVD at baseline, using Cox proportional hazards models. To examine whether MS would improve prediction of CVD beyond that achieved by its components; model fitness, discrimination and integrated discrimination improvement (IDI) statistics were used. Results: During a median follow-up of 8.6 years, there were 244 CVD events in men and 189 in women. MS resulted in HRs (95% CIs) of 1.97 (1.50 to 2.57) in men and 2.25 (1.57 to 3.21) in women after adjusting for CVD risk factors; in another model including all the five MS components, high blood pressure in both genders [men: 1.99 (1.48 to 2.67), women: 1.62 (1.14 to 2.30)), high waist circumference (≥94.5 cm) in men (1.47 (1.12 to 1.93)) and high fasting plasma glucose (FPG) in women (1.88 (1.39 to 2.55)) remained as independent predictors of CVD after adjusting for CVD risk factors. Adding the MS variable to this model did not yield any improvement in model fitness, C-statistic or significant IDI value. Conclusion: In the Middle East population, MS did not provide CVD predictive risk information beyond its individual components; clinical focus should remain on hypertension in both sexes, high FPG in women and central adiposity in men rather than MS.